The effect of short-term exercise on plasma procoagulant activity in patients with type II (non-insulin-dependent) diabetes and healthy volunteers. - Ibbotson, S; Gough, S; Rice, P; Davies, J; Grant, P (1993)
The effect of exercise on plasma coagulant activity was studied in 16 subjects with newly-diagnosed type II diabetes without vascular complications and 9 healthy volunteers. Generation of thrombin was determined by a computer-assisted chromogenic method and results expressed as time to generate 50% maximal thrombin activity (T50/s). In addition, APTT, factor VIII and thrombin-antithrombin III (TAT) complex levels were measured. Pre-exercise FVIII:C [mean (+/- SD)] was increased in diabetic compared to control subjects [1.5 (0.4); 0.9 (0.2) IU ml-1; (p < 0.001) respectively]. No significant differences in APTT, TAT or T50 were detected between the groups. Exercise induced a rise in FVIII complex, reduction of APTT [33 (2) s to 31 (2) s; (p = 0.004)] and T50 [58 (6) s to 53 (6) s; (p = 0.01)] in controls and an increase in FVIII complex but no significant changes in APTT or T50 in diabetic patients, with no change in TAT in either group. A greater increase in FVIII:C than vWF levels occurred in controls [0.2 (0.1); 0.1 (0.1) IU ml-1; (p = 0.005)] and patients [0.3 (0.4); 0.2 (0.1) IU ml-1; (p = 0.032)]. In patients, FVIII:C correlated inversely with APTT (r = -0.522, p = 0.038) and T50 (r = -0.592, p = 0.016). The results show that FVIII:C levels are increased at diagnosis in patients with type II diabetes without vascular disease but there is no enhancement of plasma procoagulant activity. In healthy individuals, exercise induced activation of coagulation which was not seen in patients, suggesting that it does not precipitate a state of accelerated thrombogenesis in subjects with uncomplicated type II diabetes.